Expanding the light absorption of poly(3-hexylthiophene) by end-functionalization with π-extended porphyrins. Issue 1 (28th October 2015) - Chevrier, Michèle; Richeter, Sébastien; Coulembier, Olivier; Surin, Mathieu; Mehdi, Ahmad; Lazzaroni, Roberto; Evans, Rachel C.; Dubois, Philippe; Clément, Sébastien
Abstract : Poly(3-hexylthiophene)s end-functionalized with π-extended porphyrins show a broad absorption profile up to 700 nm and a fibrillar microstructure tuned by the porphyrin molar ratio. Abstract : Poly(3-hexylthiophene)s end-functionalized with π-extended porphyrins have been synthesized in a one-pot procedure. The polymers show a broad absorption profile extending to 700 nm and a fibrillar microstructure, which can be tuned through judicious selection of the porphyrin molar ratio.